In planta Genome Editing in Commercial Wheat Varieties - Liu, Yuelin; Luo, Weifeng; Linghu, Qianyan; Abe, Fumitaka; Hisano, Hiroshi; Sato, Kazuhiro; Kamiya, Yoko; Kawaura, Kanako; Onishi, Kazumitsu; Endo, Masaki; Toki, Seiichi; Hamada, Haruyasu; et al. (Frontiers in Plant Science, 2021)
Limitations for the application of genome editing technologies on elite wheat (Triticum aestivum L.) varieties are mainly due to the dependency on in vitro culture and regeneration capabilities. Recently, we developed an in planta particle bombardment (iPB) method which has increased process efficiency since no culture steps are required to create stably genome-edited wheat plants. Here, we report the application of the iPB method to commercially relevant Japanese elite wheat varieties. The biolistic delivery of gold particles coated with plasmids expressing CRISPR/Cas9 components designed to target TaQsd1 were bombarded into the embryos of imbibed seeds with their shoot apical meristem (SAM) exposed. Mutations in the target gene were subsequently analyzed within flag leaf tissue by using cleaved amplified polymorphic sequence (CAPS) analysis. A total of 9/358 (2.51%) of the bombarded plants (cv. ‘Haruyokoi’, spring type) carried mutant alleles in the tissue. Due to the chimeric nature of the T0 plants, only 6 of them were inherited to the next (T1) generation. Genotypic analysis of the T2 plants revealed a single triple-recessive homozygous mutant of the TaQsd1 gene. Compared to wild type, the homozygous mutant exhibited a 7 day delay in the time required for 50% seed germination. The iPB method was also applied to two elite winter cultivars, ‘Yumechikara’ and ‘Kitanokaori’, which resulted in successful genome editing at slightly lower efficiencies as compared to ‘Haruyokoi’. Taken together, this report demonstrates that the in planta genome editing method through SAM bombardment can be applicable to elite wheat varieties that are otherwise reluctant to callus culture.